SMORE: spatial motifs reveal patterns in cellular architecture of complex tissues - Zainalabedin Samadi; Kai Hao; Amjad Askary (Genome Biology)
Abstract Deciphering the link between tissue architecture and function requires methods to identify and interpret patterns in spatial arrangement of cells. We present SMORE, an approach to detect patterns in sequential arrangements of cells and examine their associated gene expression specializations. Applied to retina, brain, and embryonic tissue maps, SMORE identifies novel spatial motifs, including one that offers a new mechanism of action for type 1b bipolar cells. Structural signatures detected by SMORE also form a basis for classifying tissues. Together, our method provides a new framework for uncovering spatial complexity in tissue organization and offers novel insights into tissue function.